Stable aqueous nanoparticle film assemblies with covalent and charged polymer linking networks - Russell, Lesley E (Langmuir : the ACS journal of surfaces and colloids, 2007)
The construction of highly stable and efficiently assembled multilayer films of purely water soluble gold nanoparticles is reported. Citrate-stabilized nanoparticles (CS-NPs) of average core diameter of 10 nm are used as templates for stabilization-based exchange reactions with thioctic acid to form more robust aqueous NPs that can be assembled into multilayer films. The thioctic acid stabilized nanoparticles (TAS-NPs) are networked via covalent and electrostatic linking systems, employing dithiols and the cationic polymer poly(L-lysine), respectively. Multilayer films of up to 150 nm in thickness are successfully grown at biological pH with no observable degradation of the NPs within the film. The characteristic surface plasmon band, an optical feature of certain NP film assemblies that can be used to report the local environment and core spacing within the film, is preserved. Growth dynamics and film stability in solution and in the air are examined, with poly(L-lysine) linked films showing no evidence of aggregation for at least 50 days. We believe these films represent a pivotal step toward exploring the potential of aqueous NP film assemblies as a sensing apparatus